THYROID DYSFUNCTION IN NEWLY DIAGNOSED HYPERTENSIVE PATIENTS. (April 2021) - Almustafa, Bader; Alshubini, Aqeela; Alrumaih, Zainab; Aljaffer, Yasser; Alhai, Saleh; Aldubaisi, Bashayer; Alzayer, Ahmed; Alfaraj, Nada; Albabli, Afrah
Abstract: Objective: To determine the prevalence of thyroid dysfunction in patients with hypertension attending primary health care clinics in QATIF province. Design and method: Thyroid dysfunction, defined as TSH levels below 0.5 or above 3.5 mU/L, was tested in a total of 1, 092 patients with new diagnosis of HTN or DM2, from 15 Nov 2012 till 20 Sep 2017, in 3 Primary Health Care centers. Data of 20% of this population were traced by systematic random sampling to review their detailed demographic and clinical information. This included manual and electronic review of medical records. Data collected include demographics, Hx of Comorbidity, ToD and other CVR, vital measures, lipids, FBS and A1c. Data verified and cleaned for outliers, recoded and grouped. Analysis done by SPSS including Univariate, Bivariate, Crosstab, chi square and binary logistic regression for Thyroid Dysfunction. Results: TFT and basic demographic and clinical data were traceable in 163/185 (88.1% of the sample). Females constitute 61.3% while obesity 60.4%, Mean Age 50.6 (13) yrs, Hypertension 60.1%, DM2 58.3% and Dyslipidemia 73%. Prevalence rate of thyroid dysfunction was 20.3%. No statistically significant difference was noted between groups of gender, BMI, Age, being DM or HTN or having an abnormal ECG finding. Binary logistic regression showed no significant effect of any of the included independent variables, including Age, BMI Level, pulse, SBP, DBP, DM, FBS, Dyslipidemia, T. Cholesterol, LDL, HDL, Triglyceride, sex, Age Group, DBP by SBP and T. Cholesterol by LDL by Triglyceride. However, 97% of the them were at age of 35 or above. Conclusions: In newly diagnosed CMR patients, 20.9% are having Thyroid dysfunction. It was unpredictable by Hx, demographics, ToD and other CVR. TFT may be a must to-do test in these patients, regardless of their demographic and clinical presentations.